Application of Information Theory to Computer Vision and Image Processing - Flores-Fuentes, Wendy; Sergiyenko, Oleg; Rodríguez-Quiñonez, Julio C.; Miranda-Vega, Jesús E. (Entropy (Basel, Switzerland), 2024)
Our perception of the world is the product of the human visual system's complex optical and physical process [...].Our perception of the world is the product of the human visual system's complex optical and physical process [...].